Adrenalectomy to treat reactivated chronic hepatitis B infection in a patient with a steroid-secreting adrenal tumour. (20th January 2011) - Smith, P J; Suri, D
Abstract : We present a case of reactivation of chronic hepatitis B virus (HBV) infection by a steroid-producing adrenal tumour. The tumour caused a reactivation and subsequent flare of the patients' HBV. The adrenal tumour was treated with an adrenalectomy and as a consequence the patients' transaminitis and viral load fell rapidly without the need for any additional hepatitis B treatment. The role of hepatitis B and steroid priming is discussed and the possible immunological mechanisms that underpin this phenomenon.